Functionality-switchable terahertz metamaterial with perfect absorption and circular dichroism. (1st September 2022) - Liang, Shuang; Zhu, Zebin; Jiang, Liyong
Abstract: Terahertz functionality-switchable devices have drawn more and more attention in the past few years. Here we report a graphene-VO2 based planar terahertz metamaterial model which can support switchable functions between perfect absorption and circular dichroism (CD) by changing the phase of VO2 . In particular, when VO2 is in the metal phase or insulator phase, the device can respectively work as a broadband perfect absorber with maximum absorption larger than 99% or an absorber with a CD value as high as about 0.5 for the left-handed polarized and right-handed polarized beams. We employ the coherent light absorption theory and mode coupling model of the U-shaped resonators to interpret the underlying mechanism of the device. Meanwhile, the performance of the device can be modulated on purpose by changing the chemical potential of graphene or the thickness of the SiO2 spacer layer.